The Effect of Curing Pressure and Duration on Mechanical Strength of Ultrahigh Molecular Weight Polyethylene/High-Density Polyethylene Composite as An Alternative Material for Windmill Turbine - Febrianti Nurul Hidayah; Johan Boss (Rekayasa, 2020)
The use of steel in building or construction manufacture continues to decrease, owing in part to the sustainability and mechanical properties of fibers which have higher strength in minimum weight than steel. This preliminary study was defined to evaluate the mechanical properties of high-performance fibers, especially ultrahigh molecular weight polyethylene (UHMWPE), in terms of the composite to be the main material of windmill turbines. It was UHMWPE as reinforcement and high-density polyethylene (HDPE) as a matrix in this composite system. The composites were processed in a variety of pressure and duration (50 to 165 bar and 10 minutes to 48 hours). The mechanical strength was tested by 3-point bending tests to measure the interlaminar shear strength, shear modulus, and bending strength. The result showed a significant difference in properties of the composite which is higher pressure and longer duration obtained a higher value of mechanical strength.